Design and construction of a smart lock system using Internet of Things (IoT) - Muhammed Abudu Aniru; Enoma Victor Osasenaga; Osamwonyi Efosa Emmanuel; Matthew Onyeka Gerald; Emede Oghenekome Melody (Universitas Komputer Indonesia, 2025)
This study designs and constructs an Internet of Things (IoT)-based smart door lock system to enhance home security and accessibility. Traditional manual lock systems are often slow, insecure, and highly vulnerable to breaches. The proposed system integrates a NodeMCU ESP8266 microcontroller, a solenoid lock, a 12V DC battery, a 5V buck converter (LM7805), a Wi-Fi module, and relay switches to offer a robust protection mechanism. Testing involved three independent devices across ten trials. In all trials, the system accurately interpreted remote commands and transmitted signals to the relay module, successfully triggering the solenoid lock mechanism. This confirms the system's effectiveness in providing secure, keyless, and automated remote access control.